Managing viruses in onion and garlic - Gawande, S J; Singh, Major (Indian Horticulture, 2019)
Onion and garlic are the spice and vegetable crops of prime importance inIndia and other parts of the world. Viruses are among the major constraintsin onion and garlic in exploiting their yield potential. Of 16 major viruses,genus, Tospovirus, Potyvirus, Allexivirus, Carlavirus and Potexvirus are knownto infect onion and garlic. Worldwide, these viruses causes significant lossesin both onion and garlic. Iris yellow spot virus (IYSV) causes up to 100%yield loss in seed onion crop. Similarly, in garlic, up to 88% reduction ofbulb weight is reported by potyviruses only.